Best Practices for Culinary Medicine Programming - Andrea Krenek; Anne Mathews; Wendy Dahl (EDIS)
Nutrition and lifestyle habits are recognized as essential for health across the lifespan. A new approach to promote healthy practices is through culinary medicine (CM) or culinary nutrition (CN) programs. The optimal content, format, and timing varies across types of CM/CN programs. The purpose of this new 6-page publication of the UF/IFAS Food Science and Human Nutrition Department is to provide an overview of CM/CN and best practices for implementation by nutrition educators with a range of populations. Written by Andrea Krenek, Anne Mathews, and Wendy Dahl. https://edis.ifas.ufl.edu/fs445